The Study of Eco-Theological Hadits: Integrating Islamic Ethical Values in Environmental Conservation - M. Fatchurrohman; Yetty Faridatul Ulfah; Agus Fatuh Widoyo; Faruq Alhasbi; M. Farhan Ubaidillah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyse the potential of the Prophet Muhammad's hadith as a source of Islamic environmental ethics through an eco-theological approach in the context of contemporary environmental conservation. This study was library research, with the main data in the form of ecologically nuanced hadiths that are analysed thematically and contextually. The analysis was conducted within the framework of the theological relationship between God, humans, and nature to uncover the environmental ethical values contained in the hadith. The results reveal that the Prophet's hadith contain comprehensive environmental ethical principles, including the concepts of caliphate and trust, the prohibition of causing damage (fasād), the principles of cleanliness, moderation (wasathiyah), balance (mīzān), and the protection of living creatures. These values emphasize that environmental preservation is an integral part of the responsibility of faith and ethical practice of Muslims. In terms of novelty and contribution, this study offers a formulation of a systematic and applicable hadith-based Islamic environmental ethics framework, and positions the hadith as a strategic normative source in supporting environmental conservation and sustainable development.